Study of Alternatives for Meeting the Demand of Raw Material by Wood-based Industries - Ahmed, Parvez (Indian Forester, 2005)
Industrial development in the country has led to setting up of a number of paper, plywood and other wood-based industries in all States leading to sharp increase in timber and pulpwood demand. Forest-based industries bave been using forest products as raw material since beginning. States allocated raw material from forests to industries at concessional prices for long periods without applying the economic yardsticks. This led to some complacency on part of the industry both in terms of not investing in raw material development and continuously using the leverage to obtain raw material at administered prices. This practice continued for long period and ultimately led to the degradation of vast areas of forests. The concern about the negative impact of wood-based industry on forest resources, has found expression in the 1988 Forest Policy, which directs state governments to stop the practice of providing forest products to industries on administered prices. Wood-based industries faced the shortages of raw material since then. The controversial move of leasing forest lands to industries for captive plantations could not get through. The objective of the present study is to investigate various options and alternatives to meet the demand of raw material by the wood-based industries on sustained basis.